Effects of hyperthermia therapy on the liver. II. Morphological observations. Issue 1 (January 1976) - Wills, E J; Findlay, J M; McManus, J P
Abstract : Liver biopsy specimens obtained from three patients during treatment of advanced malignant disease by exogenous hyperthermia were studied by light and electron microscopy. In two patients the parenchymal cells showed either slight swelling or nuclear alterations by light microscopy and, at the fine structural level, large numbers of autophagic vacuoles, dilatation of Golgi elements and endoplasmic reticulum, and large cytoplasmic vacuoles. Similar changes, but in much more severe form together with parenchymal cell necrosis and cholestasis, were seen in the liver of case 3, who developed jaundice 24 hours after hyperthermia. The findings are discussed in relation to earlier accounts of liver changes following hyperthermia, and the functional implications are considered.